Toxicity assessment of gallic acid loaded graphene oxide (GAGO) nano-formulation in zebrafish (Danio rerio) embryos - Abdul Ghafor, Ahmad Ashraful Hadi; Elias, Nurhuda; Shamsi, Suhaili; Md. Yasin, Faizah; Sarchio, Seri Narti Edayu (Universiti Putra Malaysia Press, 2020)
Gallic acid (GA) is a phenolic compound found in almost all plants and has been reported to possess powerful health benefits such as anti-oxidant, anti-inflammatory, anti-cancer, and anti-diabetic properties. However, GA suffers a short half-life when administered in vivo. Recent studies have employed graphene oxide (GO), a biocompatible and cost-effective graphene derivative, as a nanocarrier for GA. However, the toxicity effect of this formulated nano-compound has not been fully studied. Thus, the present study aims to evaluate the toxicity and teratogenicity of GA loaded GO (GAGO) against zebrafish embryogenesis to further advance the development of GA as a therapeutic agent. GAGO was exposed to zebrafish embryos (n ≥ 10; 24hr post fertilization (hpf)) at different concentrations (0-500 µg/ml). The development of zebrafish was observed and recorded twice daily for four days. The toxicity of pure GO and GA was also observed at similar concentrations. Distilled water was used as control throughout the experiment. A significantly high mortality rate, delayed hatching rate and low heartbeat were recorded in embryos exposed to GO at concentrations of ≥ 150 µg/ml at 48 hr (p<0.01), 72 hr (p<0.001) and 96 hr (p<0.0001) post-exposure. Interestingly, all measured parameters were significantly improved in embryos exposed to the same concentration of GAGO (100-150 µg/ml), which was comparable to control group at all-time points. The present data demonstrated that GAGO is safe to be used at low concentration exposure (0-150 µg/ml), but further study has to be conducted to correlate the toxicity of GAGO with its effective concentration in in vitro and in vivo model.